2022
DOI: 10.1111/bcp.15177
|View full text |Cite
|
Sign up to set email alerts
|

Concentration–response relationships of dolutegravir and efavirenz with weight change after starting antiretroviral therapy

Abstract: Dolutegravir is associated with more weight gain than efavirenz in people starting antiretroviral therapy (ART). We investigated the concentration–response relationships of efavirenz and dolutegravir with weight gain. We determined concentration–response relationships of dolutegravir and efavirenz (both combined with tenofovir disoproxil fumarate and emtricitabine) with changes in weight and fat distribution, derived from dual‐energy x‐ray absorptiometry scans, in a nested study of ART‐naïve participants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…Data from ADVANCE strongly suggests this is the case, reporting that weight gain among moderate and fast metabolizers of efavirenz was the same as that among those on the dolutegravir arm, containing the same nucleoside backbone. 26 , 27 This is supported by other studies on the impact of efavirenz concentrations on weight gain. 28 …”
Section: Discussionsupporting
confidence: 66%
“…Data from ADVANCE strongly suggests this is the case, reporting that weight gain among moderate and fast metabolizers of efavirenz was the same as that among those on the dolutegravir arm, containing the same nucleoside backbone. 26 , 27 This is supported by other studies on the impact of efavirenz concentrations on weight gain. 28 …”
Section: Discussionsupporting
confidence: 66%
“…It has been postulated that dolutegravir could cause weight gain by off-target effects through inhibition of the melanocortin-4 receptor pathway, affecting appetite and energy balance. 19 , 20 However, in vitro studies have shown that the concentrations needed for the direct inhibition of the melanocortin-4 receptor that would explain clinically important weight gain are much higher than those achieved with the currently recommended daily dose of 50 mg. 21 In a sub-study of ADVANCE, our group has recently shown that weight gain differences between dolutegravir and efavirenz are driven by impaired weight gain in participants who are genetically slow metabolisers of efavirenz 22 – this finding suggests that dolutegravir is not causing weight gain but that efavirenz is impairing weight gain in slow metabolisers who have high efavirenz concentrations. The reason for the contributory effect of TAF on weight gain is still unclear and may reflect weight loss effects of TDF.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss may be due to HIV itself, opportunistic infections or HIV-associated tumours. Failure to gain weight has been associated with efavirenz toxicity over time as was observed in a study in South Africa 30. Weight loss in both ART naïve and exposed patients has been associated with increased morbidity and mortality 31 32.…”
Section: Discussionmentioning
confidence: 92%
“…Failure to gain weight has been associated with efavirenz toxicity over time as was observed in a study in South Africa. 30 Weight loss in both ART naïve and exposed patients has been associated with increased morbidity and mortality. 31 32 A study in England observed that each log10 increase in HIV viral load was associated with a 0.92 kg decrease in body weight.…”
Section: Discussionmentioning
confidence: 99%